Analysis of Archives Storage Systems in the Logistics Division at PT. Dharma Lautan Utama Surabaya - Ceria, Septifa Nadha Lailiano; Purwanto, F. X. Adi; Purwiyanto, Didik (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2024)
This research is a qualitative research. The research methods used include document analysis, interviews, and direct observation in the field. This research aims to analyze the archival storage system in the logistics division of PT. Dharma Lautan Utama Surabaya so that archived documents can be stored properly and optimally. The research results show that the archive storage process currently used still faces challenges in terms of information accessibility, document security, and archive storage space management. Some of the efforts suggested in this research are related to implementing a digital archives management system, efficient spatial planning, using minimalist archive storage facilities, and employee training regarding document management.